Pengaruh Beberapa Faktor Risiko Terhadap Kejadian Surgical Site Infection (SSI) Pada Pasien Laparotomi Emergensi - Yuwono . (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2013)
ABSTRAK Surgical Site Infection (SSI) is a major complication of surgery which can increase morbidity,  mortality and cost of hospitality. Incidence of SSI at a healthcare provider/facility reflected a service quality of that institution. WHO reported prevalence of SSI was around 5% to 34%. Elective or emergency laparotomy is one of major surgery in a hospital. Some factors could be influence incidence of SSI were degree of contamination (kind of surgery), ASA (American Society of Anesthesiologists) score, DM (Diabetes Mellitus) co morbidity, temperature of patients, number of leukosit and duration of surgery. We aimed to explore incidence of SSI and contributing factors of emergency laparotomy patients from RSUP MH Palembang. This research was observational analytic with cross-sectional design. We found incidence of SSI 56,67% consist of incisional superficial SSI 70,6%,  incisional SSI 23,5% and organ SSI 5,9%. SSI occurred at third day until seventh day after surgery and mostly at fifth day (52,9%). Pathogen dominant in these cases were Escherichia coli 31,25%. Statistical analytic with confidence interval 95% revealed risks of ASA score (p 0.004, OR 2,4), patient’s temperature (p 0.008, OR 10,2), diabetes mellitus co morbidity (p 0.492, OR 1,87), kind of surgery (p 1.0 OR 1,36), number of leukosit (p 0.29, OR 4,80) and duration of surgery (p 0.123, OR 0,25). Conclusion: Incidence of SSI at  RSUP MH Palembang about two times compare to world average incidence of SSI. ASA score, temperature and diabetes mellitus co morbidity influenced SSI incidence. Key Words: Emergency laparotomy, risk factors, SSI